KAJIAN DESAIN ATRIUM PADA BERBAGAI DIMENSI TERHADAP DISTRIBUSI DAN PERGERAKAN UDARA PADA BANGUNAN BERLANTAI BANYAK DENGAN DENAH BUJURSANGKAR DAN BERVENTILASI ALAMI Studi Model dengan Terowongan Angin - Dian Ariestadi; Apif M. Hajji (Teknologi dan Kejuruan, 2012)
Abstract: An atrium is a type of space which is physically shaped as an enclosure inside the building. It is modified from courtyard or an opened enclosure in middle of the building. This research is conducted to identify the effect of atrium size to the air movement velocity rate and its distribution through the rooms in a square-shaped natural-ventilated high rise building. It sets a design research of atrium building and tests the models in a wind tunnel. The varieties of the atrium size are determined in three different dimensions: 12x12 sqm, 18x18 sqm, and 24x24 sqm. The experiment method used in this research utilizes the model for observing the size variety impacting the air velocity and its distribution. The outline of the projected air movement will be illustrated by using Winsurf software. The result of the tests shows that in the atrium building: (1) the air movement penetrating the workspaces has velocity average as less than 0.1 m/s or has bad quality natural ventilation; (2) the effect of atrium size to the air movement in the workspaces indicates: in top level, bigger size of the atrium leads to lower air movement velocity, in mid level, bigger size of the atrium leads to higher air movement velocity, meanwhile in the base level, bigger size of the atrium leads to higher air movement as well. However, the vertical air movement is hardly to observe, because in the atrium the air distribution tends to move circular and creates turbulence; dominated by horizontal movement rather than vertical direction to the top level ventilation outlets.